2009
DOI: 10.1063/1.3121422
|View full text |Cite
|
Sign up to set email alerts
|

Analytic response theory for the density matrix renormalization group

Abstract: We propose an analytic response theory for the density matrix renormalisation group whereby response properties correspond to analytic derivatives of density matrix renormalisation group observables with respect to the applied perturbations.Both static and frequency-dependent response theories are formulated and implemented. We evaluate our pilot implementation by calculating static and frequencydependent polarisabilities of short oligo-di-acetylenes. The analytic response theory is competitive with dynamical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
99
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(100 citation statements)
references
References 39 publications
1
99
0
Order By: Relevance
“…In addition, further conditions must also be placed on the first order changes in the left-and right-rotation matrices. In previous work, 21 it was shown that these conditions are…”
Section: B Time-dependent Dmrg Equation and Linear Response Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, further conditions must also be placed on the first order changes in the left-and right-rotation matrices. In previous work, 21 it was shown that these conditions are…”
Section: B Time-dependent Dmrg Equation and Linear Response Theorymentioning
confidence: 99%
“…This was first proposed by Dorando et al 21 in the DMRG context, and later recast in the MPS language by Haegeman et al, 24,25 by means of the time-dependent variational principle (TDVP). 23 Here, we follow Dorando's work in order to use the DMRG context in what follows.…”
Section: Brief Overview Of the Dmrg Linear Response Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, many groups have independently implemented and improved on the ab-initio DMRG algorithm. Some of these improvements include parallelization, 8,20 nonAbelian symmetry and spin-adaptation, 7,[21][22][23] orbital ordering 5,[24][25][26] and optimization, 9,27-29 more sophisticated initial guesses, 5,24,25,30,31 better noise algorithms, 5,32 extrapolation procedures, 5,33,34 response theories, 35,36 as well as the combination of the DMRG with various other quantum chemistry methods such as perturbation theory, 37 canonical transformations, 38 configuration interaction, 39 and relativistic Hamiltonians. 40 In the ecosystem of quantum chemistry, the DMRG occupies a unique spot.…”
Section: Introductionmentioning
confidence: 99%